Monolayer of silica nanospheres assembled onto ITO-coated glass substrates by spin-coating - Faraco, T. A.; Yoshioka, N. A.; Sábio, R. M. [UNESP]; da Barud, H. S.; Maciel, I. O.; Quirino, W. G.; Fragneaud, B.; de Aguiar, A. M.; Ribeiro, S. J.L. [UNESP]; Cremona, M.; Legnani, C. [UNESP] (IOP Publishing, 2021)
In this work, we synthesized colloidal silica nanospheres with an average size of 400 nm through the modified Stöber method and successfully fabricated an ordered close-packed silica nanosphere monolayer onto ITO-coated glass substrates using a three-step spin-coating method. ITO films showed resistivity comparable to that of commercial ITO and the silica nanosphere monolayer-coated ITO/glass substrate exhibited good optical transmittance in the visible (550 nm) and near-infrared (900 nm) regions of 62% and 82%, respectively. The results suggest that this monolayer can be used in optoelectronic devices to enhance efficiency in photovoltaic cells.
Keywords: ITO substrates; Silica nanospheres monolayer; SiO2 nanospheres